OPTIMALISASI DI ERA DIGITAL MELALUI POJOK BACA SEBAGAI UPAYA MENINGKATKAN MINAT BACA MASYARAKAT DI DESA URUNG PANE - Karimaliana, Karimaliana; Sari, Maya; Syafitri, Yenni; Ginting, Intan Anisa; Shafira, Aliya; Widodo, Melly Andani (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2024)
The activity of establishing a reading corner as an effort to support people's interest in reading at the Orung Paneh Village House is a form of community service in the context of increasing literacy and the need for advertising among the village community because the Orung Paneh Village House is functioning. do not provide a corner for lessons.The aim of this project is to increase community literacy by supporting a study corner and bringing reading materials closer to the community at the Urung Pane Village Hall. The digital era is a decade in which individuals have come together to use digital technology that has contributed to the development of their own cultural thinking. In the digital decade, many disruptions emerged which occurred at the intersection of social action, including literacy facilities which were able to undergo changes from the time print became digital, but the rapid flow of input and sources of valid input, created a separate response to digital literature, therefore.The part in the diagram supports motor rotation, the desire to read, and the influence of the extension of opinion knowledge through reading facilities. I define my related craft activities as using literacy using print facilities or libraries through the "Reading Corner" which includes various kinds of libraries using reliable input references. , because it is capable of following the ISBN certification, which guarantees the validity of the information contained therein, in order to maintain a registration order that agrees to use the Indonesian reference structure agrees to use EYD, and PEUBI which takes the library as a reference facility that is still concrete.Keyword: Digital Era, literacy, Reading Corner